Lost gallstones during laparoscopic cholecystectomy as a common but underestimated complication—case report and review of the literature - Danhel, L.; Fritz, A.; Havranek, L.; Kratzer, T.; Punkenhofer, P.; Punzengruber, A.; Rezaie, D.; Tatalovic, S.; Wurm, M.; Függer, R.; Biebl, M.; Kirchweger, P. (Frontiers in Surgery, 2024)
Laparoscopic cholecystectomy (LC) represents one of the most commonly performed routine abdominal surgeries. Nevertheless, besides bile duct injury, problems caused by lost gallstones represent a heavily underestimated and underreported possible late complication after LC.Case report of a Clavien-Dindo IVb complication after supposedly straightforward LC and review of all published case reports on complications from lost gallstones from 2000-2022. An 86-year-old patient developed a perihepatic abscess due to lost gallstones 6 months after LC. The patient had to undergo open surgery to successfully drain the abscess. Reactive pleural effusion needed additional drainage. Postoperative ICU stay was 13 days. The patient was finally discharged after 33 days on a geriatric remobilization ward and died 12 months later due to acute cardiac decompensation.Intraabdominal abscess formation due to spilled gallstones may present years after LC as a late complication. Surgical management in order to completely evacuate the abscess and remove all spilled gallstones may be required, which could be associated with high morbidity and mortality, especially in elderly patients. Regarding the overt underreporting of gallstone spillage in case of postoperative gallstone-related complications, focus need be put on precise reporting of even apparently innocuous complications during LC.